2012
DOI: 10.1186/1757-7241-20-53
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the quality of basic life support provided by rescuers trained using the 2005 or 2010 ERC guidelines

Abstract: IntroductionEffective delivery of cardiopulmonary resuscitation (CPR) and prompt defibrillation following sudden cardiac arrest (SCA) is vital. Updated guidelines for adult basic life support (BLS) were published in 2010 by the European Resuscitation Council (ERC) in an effort to improve survival following SCA. There has been little assessment of the ability of rescuers to meet the standards outlined within these new guidelines.MethodsWe conducted a retrospective analysis of the performance of first year healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
6
1
2
Order By: Relevance
“…Among the most frequently cited training locations are the qualified training centers (21.8%) and the Portuguese Red Cross (23.5%), different from data found in other studies (16,(20)(21)(22) . In a study conducted through telephone interviews with 7,320 respondents, the most common sources of training in first aid, more specifically in burns, were books (41.7%) and the internet (32.9%).…”
Section: Discussioncontrasting
confidence: 55%
“…Among the most frequently cited training locations are the qualified training centers (21.8%) and the Portuguese Red Cross (23.5%), different from data found in other studies (16,(20)(21)(22) . In a study conducted through telephone interviews with 7,320 respondents, the most common sources of training in first aid, more specifically in burns, were books (41.7%) and the internet (32.9%).…”
Section: Discussioncontrasting
confidence: 55%
“…This theory is supported by results of Jones et al, who showed an increase in compression frequency in 2010 CPR guideline educated students as compared to 2005 guideline educated students. [35]…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported by Roessler et al [2], Kobayashi et al [3], and Lubrano et al [5] that the time taken to initiate chest compressions can be shortened when the new guidelines were followed. Although the 2010 ERC guidelines and the 2010 AHA guidelines for BLS are different in terms of procedures for checking the victim for a response and the time taken to activate the emergency response system and initiate chest compressions, we showed that all subjects achieved a shorter chest compression initiation time after completing their re-education according to the new AHA guidelines [6][7][8][9][10][11][12][13][14]. At the time when 2005-BLS was developed, health care providers were considered not to have ventilation equipment for cardiopulmonary arrest, indicating that BLS may have actually been performed without rescue breathing.…”
Section: Discussionmentioning
confidence: 76%